SISTEM STEGANOGRAFI DENGAN METODE LEAST SIGNIFICANT BIT (LSB) TERACAK - Yohanes Julianto; Kristoforus jawa bendi (Jurnal Ilmiah Flash, 2016)
Information security has become important today. Steganography is one of the ways tomake any information secure. It hides information by inserting it in a media or cover. LSB (LeastSignificant Bit)steganographic technique has become popular because of its simplicity. LSB(Least Significant Bit) is one algorithm from steganography. The weakness of LSB is bits ofembedded are inserted sequentially. It can be easily tracked. Our research using text as embeddedmessage and WAV audio format as cover-object. We combine LSB and LCG (Linear CongruetialGenerator) to determinant the random position of replacement bit. Outcome of this research is asoftware that was develop by waterfall model and coded in Visual Basic. The result shows thatembedded message can be encode dan decode